Changing from intermittent to continuous water supply and its influence on service level benchmarks: a case study in the demonstration zone of Nagpur, India. Issue 7 (9th August 2017) - Hastak, Shashikant; Labhasetwar, Pawan; Kundley, Priya; Gupta, Rajesh
Abstract: A dearth in infrastructure and operations significantly reduces the expected benefits of safe drinking water provision. Intermittent water supplies are characterized by inefficient demand and supply management owing to operational inadequacies eventually causing physical deterioration of infrastructure and inconvenience to consumers, resulting in consumer dissatisfaction. Conversion from intermittent to continuous water supply was undertaken in a demonstration zone of Nagpur, India, with a population of about 150, 000 people. Data related to the infrastructural, operational, managerial and financial capabilities were used to determine service level benchmarks (SLBs) — pre- and post-intervention — to quantify the improvement due to continuous water supply interventions. The post-intervention data analysis clearly indicated substantial improvement in post-intervention SLBs, consequently paving the way for the conversion of the water supply of the entire city to continuous mode.